Family Functioning and Mental Health of Transgender and Gender-Nonconforming Youth in the Trans Teen and Family Narratives Project. Issue 4 (13th June 2018) - Katz-Wise, Sabra L.; Ehrensaft, Diane; Vetters, Ralph; Forcier, Michelle; Austin, S. Bryn
Abstract : Transgender and gender-nonconforming (TGN) youth are at increased risk for adverse mental health outcomes, but better family functioning may be protective. This study describes TGN youth's mental health and associations with family functioning in a community-based sample. Participants were from 33 families (96 family members) and included 33 TGN youth, ages 13 to 17 years; 48 cisgender (non-transgender) caregivers; and 15 cisgender siblings. Participants completed a survey with measures of family functioning (family communication, family satisfaction) and mental health of TGN youth (suicidality, self-harm, depression, anxiety, self-esteem, resilience). TGN youth reported a high risk of mental health concerns: suicidality (15% to 30%), self-harm (49%), clinically significant depressive symptoms (61%); and moderate self-esteem ( M = 27.55, SD = 7.15) and resiliency ( M = 3.67, SD = 0.53). In adjusted models, better family functioning from the TGN youth's perspective was associated with better mental health outcomes among TGN youth (β ranged from −0.40 to −0.65 for self-harm, depressive symptoms, and anxious symptoms, and 0.58 to 0.70 for self-esteem and resiliency). Findings from this study highlight the importance of considering TGN youth's perspectives on the family to inform interventions to improve family functioning in families with TGN youth.